Amniotic Fluid Stem Cells and Their Application in Cell-Based Tissue Regeneration - Mohamadreza Baghaban Eslaminejad; Shahrbanoo Jahangir (International Journal of Fertility and Sterility, 2012)
Advances in stem cell biotechnology hold great promise in the field of tissue engineering and regenerative medicine. Of interest are marrow mesenchymal stem cells (MSCs), embryonic stem cells (ESCs), and induced pluripotent stem cells (iPSCs). In addition, amniotic fluid stem cells (AFSCs) have attracted attention as a viable choice following the search for an alternative stem cell source. Investigators are interested in these cells because they come from the amniotic fluid that is routinely discarded after birth. There have been multiple investigations conducted worldwide in an attempt to better understand AF-SCs in terms of their potential use in regenerative medicine. In this review we give a brief introduction of amniotic fluid followed by a description of the cells present within this fluid. Their history related to stem cell discovery in the amniotic fluid as well as the main characteristics of AF-SCs are discussed. Finally, we elaborate on the potential for these cells to promote regeneration of various tissue defects, including fetal tissue, the nervous system, heart, lungs, kidneys, bones, and cartilage.